(untitled) (Journal of Bhuwanishankar, 2022)
This study aims to examine the relationship between ownership structure, deregulation, and bank risk in Nepalese commercial banks. In the study, the non-performing loan has been considered as a response variable and ownership structure, bank size, bank age, and bank regulation have been taken as independent variables. The study is based on the secondary data of 20 commercial banks with 140 observations for the period from 2012 to 2018, employing descriptive and inferential statistical tools for the analysis. The correlation analysis reveals the significant and positive relationship of age with risk, which indicates that the bank’s risk increases as the bank gets older. The study also signifies that the non-performing loans can be decreased with the implementation of capital regulation imposed by the regulatory body. The regression analysis depicts the negative and significant impact of bank size on bank risk when regressed together with the bank age. The mean value of non-performing loan for foreign-owned banks and private-owned banks is lower in comparison to that of government-owned banks. Similarly, the mean value of the non-performing loan for the deregulated period is higher in comparison to that of banks during the regulated period. The results provide interesting insights into the ownership structure and bank regulation in connection with bank risk. Hence this paper attempted to fill the gap in the existing literature in the context of Nepal. The study also elucidates that the banking business is not free from risk, and hence it has to consider a substantial number of factors while managing the risk.